2004
DOI: 10.1063/1.1664028
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hydrogen dilution on the microstructural and optoelectronic properties of B-doped nanocrystalline Si:H thin films

Abstract: We report on the roles of hydrogen dilution on the microstructural and optoelectronic properties of boron-doped nanocrystalline silicon thin films grown by plasma-enhanced chemical vapor deposition on glass substrates, through x-ray diffraction, scanning electron microscope, Raman scattering, optical transmission, temperature-dependent dark conductivity, and elastic recoil detection analysis (ERDA) measurements. The grain size, crystallinity, absorption coefficient, refractive index, and conductivity are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, for the PECVD samples the boron doping efficiency, which is the ratio of the carrier concentration to the boron concentration in the solid phase, is also very low (10-20%) [12]. Therefore, the highest conductivity hitherto reported for p-type nc-Si:H prepared by PECVD is only around 10 S/cm [12,13], whereas for HWCVD p-type nc-Si:H a conductivity value as high as 100 S/cm has been reported [14,15], which is ten times higher than the PECVD samples. Therefore, HWCVD is becoming a promising method to achieve highly conductive p-type nc-Si:H films.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, for the PECVD samples the boron doping efficiency, which is the ratio of the carrier concentration to the boron concentration in the solid phase, is also very low (10-20%) [12]. Therefore, the highest conductivity hitherto reported for p-type nc-Si:H prepared by PECVD is only around 10 S/cm [12,13], whereas for HWCVD p-type nc-Si:H a conductivity value as high as 100 S/cm has been reported [14,15], which is ten times higher than the PECVD samples. Therefore, HWCVD is becoming a promising method to achieve highly conductive p-type nc-Si:H films.…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that the grain size increased from 11.4 to 45.6 nm with decreasing the silane concentration from 13 to 4%. It is reported that hydrogen is supposed to enhance the surface diffusion of adsorbed precursors, preferentially etch off the disordered phase, and assist Si-Si bonding reconstruction within a subsurface layer [11,12]. As expected, H 2 dilution is a very sensitive method to realize crystallization of the amorphous Si thin films.…”
Section: Methodsmentioning
confidence: 61%
“…The nanocrystalline silicon growth resulted from a complex synergy between surface and bulk reactions of impinging SiH x radicals, atomic hydrogen, and ion species. 30,31 As we can see from Table I,…”
Section: Structure Evolution and Mechanism Of Oxidationmentioning
confidence: 83%